Cast Simulation and Manufacturing Constraints for Detailed Part Optimization - Nilipour Tabatabaei, Alireza; Krishnaswamyreddy, Chetan (My University, 2017)
Structural optimization and cast simulation tools has gained significant importance in automotive industry. The industry is slowly transforming into CAE driven design process, as the acceptance of CAE simulations in providing new and inspiring lighter designs with shortened development cycles is demonstrated in recent times. Optimization has become an integral part of design, there has been a demand for optimization of aluminum cast parts where engineers are challenged to guarantee both functionality and cast-ability of the component. On the other hand, casting simulation finds its applications in later part of design process particularly used by foundries for optimization of casting process by mold flow and solid simulation. The purpose of this master thesis is to propose a methodology with emphasis on application of manufacturing constraints in the topology optimization and investigate the possibility of integrating cast simulation tools in optimization driven product development. In addition, to decrease the lead development time and number of iterations in design modifications to verify cast-ability of the components. Use of casting simulation among engineers is rather new and it helps CAE and design engineers to understand the process and identify the defects and problems in early concept phase, so that there is enough time and flexibility to make changes and evaluate different concepts and aid them in choosing the best possible design. Optistrut is a finite element based structural analysis software, used to study structural topology optimization and NovaFlow&Solid is a finite volume based CFD simulation tool, used to study solidification and filling process in casting for evaluating the generated concepts from different manufacturing constraints. The proposed integrated component development process is verified on a simple and complex components, rear upper control arm (RUCA) and rear lower control arm (RLCA), respectively. The results of evaluation study confirms that the method works well in generating light weight concepts for RUCA with simple load cases without the design realization step. However, for RLCA with complex load case seems to generate bit heavy concepts than the current design, which confirms that CAD design realization loops involving CAD engineer can not be eliminated even when manufacturing constraints have been implemented. The thesis also put forward a template for calculation of threshold for optimal extraction of density plots. Different concepts from topology optimization are compared based on the cast simulations results and the results are discussed and future work is proposed. Keywords: Cast simulation, Topology optimization, Chassis components, Weight reduction, Cast components, Optistruct, NovaFlow&Solid.
Keywords: Teknisk mekanik; Grundläggande vetenskaper; Produktion; Applied Mechanics; Basic Sciences; Production